Dynamics of Policy Adoption with State Dependence - David R. Agrawal; Gregory A. Trandel (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study the dynamics of policy diffusion when a first-moving jurisdiction that legalizes an activity reduces the probability of legalization in nearby later-acting jurisdictions. If a jurisdiction's firms can sell to neighboring residents, but if the good is competitively sold at every location, then policies converge: all jurisdictions legalize or all jurisdictions ban. If firms have some market power, and if the location of firms depends on the order of legalization, an early-adopting government may legalize, but an otherwise identical, but later-acting, neighboring government might not. This possible asymmetry is due to state dependence resulting from the initial distribution of firms following the first-mover's legalization. Empirically, counties that legalize the sale of fireworks first have more firework vendors just inside their border than counties that legalize later. Furthermore, counties have a longer duration to legalize fireworks if nearby counties have already adopted. State dependence resulting from a first-mover advantage contributes to the policy divergence of regulatory policies.
Keywords: H70; K20; L50; R30; R50; 330; dynamics; fiscal competition; state dependence; externalities; borders